Макулопатия как осложнение при локальных методах лечения меланом хориоидеи - А. Е. Заргарян (Հայաստանի ԳԱԱ)
Անոթաղանթի մելանոմայի լոկալ քայքայման եղանակը կոնտակտային ռադիոակտիվ ճառագայթման միջոցով առաջացել է 1930թ. : Նրա ցուցումների ընդլայմանը զուգահեռ`գրականության մեջ ավելի շատ են սկսել արտացոլվել ռադիացիոն բարդությունները աչքի հյուսվածքների կողմից, որոնցից ճառագայթային մակուլոպաթիան՝ տեսողության սրության կորստի ամենահիմնական պատճառն է: The method of local destruction of choroidal melanoma by means of radioactive contact irradiation appeared in 1930. Along with the widening of indications for its application, more and more attention is paid to the radiation- associated complications of ocular tissues, among which the radiation-induced maculopathy presents itself as the basic cause for practically irreversible loss of the vision.
Keywords: Medicine; RE Ophthalmology